Novel route of synthesis of ultra-small Au nanoparticles on SiO2 supports. (15th January 2019) - Kotolevich, Y.; Martynyuk, O.; Martínez-González, S.; Tiznado, H.; Pestryakov, A.; Avalos Borja, M.; Cortés Corberán, V.; Bogdanchikova, N.
Abstract: A novel route to prepare monodispersed 1–2 nm gold nanoparticles (NPs), based on the use of extremely small SiO2 NPs (2–4 nm) as a support and increasing their metal-support interaction with surface modifier oxides is presented. The influence of modifier (La, Ce and Fe oxides) and modification method (impregnation ( i ) or direct synthesis ( s )) on the formation of ultra-small Au NPs and their structural and electronic properties was studied. The samples were characterized by N2 adsorption (BET), FTIR of adsorbed CO, XRD and HR-TEM methods, and tested for the catalytic selective oxidation of 1-octanol. Preparation of monodispersed Au NPs with 1 nm diameter was successfully achieved for all the modified samples studied, with exception of Au/Ce/SiO2 - i, where CeO2 was not homogeneously distributed. The Au NPs have high degree of monodispersity and are stable when treated in H2 up to 300 °C. Formation of these Au NPs depended on the strong interactions between the cationic gold complex precursor and the surface of modified SiO2 NPs. Modifiers changed electronic properties of supported gold; favoring the formation and stabilization of Au δ+ states, which are probable gold active sites of selective liquid-phase oxidation of alcohols in redox catalytic processes. 1-octanol oxidation was used as a model reaction for oxidation of fatty alcohols obtained during biomass transformation. The best performance for 1-octanol oxidation was found for gold nanoparticles supported on the ultra-small SiO2 modified cerium oxide by impregnation method. The relative order of activity was: AuCeSiO2 - i  > AuFeSiO2 - i  ≫ AuLaSiO2 - i ≈  AuLaSiO2 - s  > AuSiO2  > AuFeSiO2 - s ≫ AuCeSiO2 - s . The obtained results open the possibility of further development of high-performance catalysts for conversion of secondary products of biomass processing into valuable chemicals.